Pengaruh Strategi Membaca Nyaring Scanning Dalam Kemampuan Membaca Pemahaman Buku Cerita Pembelajaran Bahasa Indonesia Di Kelas IV SD N PAGARBATU II Sumenep - Hidayati, Gita Mukrin; Pratikno, Ahmad Sudi (Universitas Hamzanwadi, 2024)
The problem that most often occurs is that the reading comprehension ability in class IV of SD N PAGARBATU II is still low because the teacher explains the learning material. The students don't listen. understanding Indonesian language learning storybooks. Researchers used a descriptive qualitative approach. The sampling technique used purposive sampling technique with consideration of certain things or aspects. The sample in the study was all fourth grade students with a total of 10 students, namely 7 male students and 3 female students. The research was carried out by researchers at SD N PAGARBATU II Sumenep. Data collection techniques use interviews, observation and documentation. Then the research instruments used were interview guide sheets, observation guide sheets, and documentation recording equipment. The data analysis technique in this research uses the Miles and Huberman model data analysis technique, which is a data analysis technique that is carried out interactively and runs continuously until the data becomes saturated. 3 Miles and Huberman model data analysis techniques in the form of data reduction, data presentation, and drawing conclusions/verification. In this research, source triangulation and technical triangulation were used to check the validity of the data obtained by cross-checking data from various sources. Based on the results of research that has been carried out regarding the problem of reading comprehension ability with solutions from researchers, the influence of the reading aloud scanning strategy on the ability to read and understand Indonesian language learning storybooks is that it influences the ability to read comprehension at SD N PAGARBATU II Sumenep. With the data obtained, initially there were only 3 students, now it has changed to 9 students. The solution carried out by the researcher was declared successful because it experienced a significant change from initially only 30% to 90% with the initial number of 3 students changing to 9 students.